Bronchospasm Diagnosis in Motorcycle Taxi Drivers Exposed to Automotive Pollutants in Porto-Novo - Messan, Folly; LAWANI, MOHAMED MANSOUROU (My University, 2013)
by motorcycle taxi drivers. In Benin, studies conducted on motorcycle drivers, have shown the presence of nitrogen oxides, carbon monoxide, sulfur dioxide, volatile organic compounds and particulate matter in ambient air, which may affect lung function. Aims: This study aims to diagnose potential respiratory problems among 48 motorcycle taxi dri- vers (47.02 ± 8.75 years) compared to a control group made up of 52 people (46.38 ± 8.81 years) in Porto-Novo, Benin. Methods: A questionnaire, two exploration pulmonary function tests and two 6-minute walk tests were used to identify symptoms and changes in respiratory variables that reveal the existence of bronchospasm. Results: The frequency of respiratory symptoms noted among motorcycle taxi drivers is higher than that recorded among members of the control group. We observed that motorcycle drivers at rest and after physical effort have significantly lower respiratory vari- ables (FVC, FEV1, PEF, FEF25-75, FEF50 and FEF25) (p < 0.05) than those recoded in control group. Conclusion: It can therefore be concluded that, because of the relatively long duration of exposure among motorcycle taxi drivers, the in- halation of automobile pollutants, may cause respiratory problems in this population.
Keywords: Automobile Pollution; Asthma; Bronchospasm; Urban Pollution; Motorcycle-Taxi Drivers; Benin